Overcoming the Academic Failure of Students as a Priority of Educational Policy: The Case of Russia - Garold E. Zborovsky; Polina A. Ambarova; Nina V. Shabrova (Интеграция образования)
Introduction. One of the priorities of the modern educational policy of Russia is to ensure the academic success of young students – schoolchildren and university students. However, the realization of this goal is in conflict with other objectives of educational policy and factors in the development of Russian higher education, including initiatives in the field of school education. Traditionally, academic failure is interpreted as an individual’s phenomenon related to the inefficiency of pedagogical approaches and technologies. However, in fact, the social scale and context of the problem make it necessary to consider it as an institutional phenomenon, the prerequisites of which are formed at the level of pre-university education. The purpose of the article is to interpret the problem of academic failure of students in the context of educational policy.